A Comparative Qualitative Case Study on Employee Wellness Programs using Discovery and Johnson & Johnson - Nyoni, Zandile (The IIE, 2017)
Employee wellness has been identified as one of the leading factors contributing towards organisational performance. Discovery is the largest medical aid provider within South Africa and Johnson & Johnson are the leader in consumer goods within South Africa. The aim of the study is to explore employee wellness programs within Discovery and Johnson & Johnson providing an insight into the types of employee wellness programs used in these organisations. The research design used in this research is a qualitative case study. Content analysis is the selected data analysis tool and a coding scheme was used to code the data in the research. The first main finding found in the research is employee wellness programs are tools to retain and attract employees within the organisation. The second finding found in the research is employee wellness programs have the ability to yield a higher return on investment for the organisation and are not simply a corporate expense. The third finding found in the research is having an organisational culture that supports the use of employee wellness programs within the organisation will lead to a decrease in absenteeism within the organisation. The last finding found is that employee wellness programs have the ability to increase organisational performance and increase employee wellness within an organisation.
Keywords: Employee wellness; Organisational performance; Wellness programs; Organisational culture